RNA-Seq Analysis of the Effect of Zinc Deficiency on Microsporum canis, ZafA Gene Is Important for Growth and Pathogenicity - Dai, Pengxiu; Lv, Yangou; Gong, Xiaowen; Han, Jianye; Gao, Peng; Xu, Haojie; Zhang, Yihua; Zhang, Xinke (Frontiers in Cellular and Infection Microbiology, 2021)
Microsporum canis, a common pathogenic skin fungus, can cause dermatophytosis in humans and animals. Zinc is an important trace element and plays an important role in the growth and metabolism of fungi. Currently, the effects of zinc deficiency on growth, gene expression, and metabolic pathway have not been clarified in M. canis. Therefore, M. canis was cultured under zinc restriction, and RNA-Seq was conducted in this study. The growth of M. canis was severely inhibited, and many genes showed significant upregulation and downregulation in M. canis with zinc deficiency. Zinc deficiency could negatively affect the gene expression and biological metabolic pathway in M. canis. The zinc-responsiveness transcriptional activator (ZafA) gene was significantly upregulated and shared homology with Zap1. Thus, the ZafA gene might be the main transcription factor regulating M. canis zinc homeostasis. The ZafA gene knockout strain, ZafA-hph, was constructed via Agrobacterium tumefaciens-mediated transformation (ATMT) in M. canis for the first time to assess its function. In vitro growth ability, hair biodegradation ability, virulence test, and zinc absorption capacity in ZafA-hph and wild-type M. canis strains were compared. Results showed that the ZafA gene plays an important role in zinc absorption, expression of zinc transporter genes, and growth and pathogenicity in M. canis and can be used as a new drug target. Cutting off the zinc absorption pathway can be used as a way to prevent and control infection in M. canis.